2015
DOI: 10.1007/s13213-015-1106-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and fermentation conditions of highly acetoin-producing acetic acid bacterium from Liangzhou fumigated vinegar in China

Abstract: Liangzhou fumigated vinegar is famous in China for its distinct flavor. How to enhance flavor in traditional fermented foods, such as vinegar, has attracted a large interest in recent years. Acetoin (ACT) is a precursor of tetramethylpyrazine (TTMP), a popular food flavor found in different traditional fermented foods. We obtained 200 acid-producing isolates from the solid fermentative substrate of Liangzhou fumigated vinegar by the method of forming transparent zones on GYC agar, and 28 bacteria producing ACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, 2,3-butanediol is positively correlated with Lactobacillus and Streptococcus during wine fermentation ( Chen et al, 2020 ). Acetobacter pasteurianus has high acetoin production capacity ( Zhao and Yun, 2016 ). Therefore, 2,3-butanediol and tetramethylpyrazine formation may be related to Acetobacter pasteurianus as well as.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 2,3-butanediol is positively correlated with Lactobacillus and Streptococcus during wine fermentation ( Chen et al, 2020 ). Acetobacter pasteurianus has high acetoin production capacity ( Zhao and Yun, 2016 ). Therefore, 2,3-butanediol and tetramethylpyrazine formation may be related to Acetobacter pasteurianus as well as.…”
Section: Resultsmentioning
confidence: 99%
“…It is a key flavor substance in vinegar (Lu et al, 2016). Some studies have demonstrated that Acetobacter cocultured with Lactobacillus simulated the fermentation of vinegar and that Acetobacter promoted the accumulation of acetoin, which was also enhanced in cocoa bean fermentation (Chai et al, 2020; Moens et al, 2014; Zhao & Yun, 2015). Studies have suggested that lactic acid produced by Lactobacillus is transformed into acetoin by Acetobacter during co‐fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al inoculated Bacillus amyloliquefaciens producing acetoin and TMP at a high level in the fermentation starter and elevated the acetoin and TMP contents in Baoning bran vinegar [ 22 ]. Zhao and Yun screened highly acetoin-producing AAB from the solid substrate of Liangzhou fumigated vinegar in order to apply these strains in the industrial production of vinegars [ 23 ]. Chai et al accelerated the acetoin and TMP production in the vinegar fermentation process through Lactobacillus sp.- A. pasteurianus joint bioaugmentation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%